Zombie as (counter)cultural metaphor - Ferrero, Ángel; Roas, Saúl (Nómadas. Critical Journal of Social and Juridical Science, 2011)
In the last decade zombie films have not only experienced a comeback with critical acclaim as much as box-office success, but also spawned a large specialized literature and entered in the social consciousness. Thus, the figure of the zombie has become a social metaphor. The article sets a cartography of the genre, explores the causes of this sociocultural phenomenon and explains the origin and evolution of the undead as a social metaphor in several contexts of social, political and economic crisis, from the classics White Zombie (Victor Halperin, 1932) and Night of the Living Dead (G.A. Romero, 1968) to the most recent films.
Keywords: horror film; genre; film; zombie; social metaphor.